Modulation of surface physics and chemistry in triboelectric energy harvesting technologies - Bo-Yeon Lee; Dong Hyun Kim; Jiseul Park; Kwi-Il Park; Keon Jae Lee; Chang Kyu Jeong (Science and Technology of Advanced Materials, 2019)
Mechanical energy harvesting technology converting mechanical energy wasted in our surroundings to electrical energy has been regarded as one of the critical technologies for self-powered sensor network and Internet of Things (IoT). Although triboelectric energy harvesters based on contact electrification have attracted considerable attention due to their various advantages compared to other technologies, a further improvement of the output performance is still required for practical applications in next-generation IoT devices. In recent years, numerous studies have been carried out to enhance the output power of triboelectric energy harvesters. The previous research approaches for enhancing the triboelectric charges can be classified into three categories: i) materials type, ii) device structure, and iii) surface modification. In this review article, we focus on various mechanisms and methods through the surface modification beyond the limitations of structural parameters and materials, such as surficial texturing/patterning, functionalization, dielectric engineering, surface charge doping and 2D material processing. This perspective study is a cornerstone for establishing next-generation energy applications consisting of triboelectric energy harvesters from portable devices to power industries.